Social and Economic Impact Evaluation of Gender Based Community Empowerment - Reiki Nauli Harahap; Yudith Ramaniya; Herlan Herlan; Annisa Rizqa Alamri; Zainal Fadri (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2023)
Social and economic impact measurement is an activity that cannot be separated from corporate social responsibility programs. Measuring socioeconomic impacts has a variety of approaches, one of which is the community satisfaction index. This study aims to measure the social and economic impact of the Kelompok Wanita Tani: Kartini Kalongan program, a CSR program that targets women as beneficiaries. This research uses mix methodes with quantitative as the main method and qualitative as the supporting method. The results of the study stated that the KWT CSR program: Kartini Kalongan as one of the gender-based empowerment programs has a very good level of fissibility. The program is able to answer the needs, potentials and problems faced by beneficiaries and is supported by the company's commitment to contribute to the development of the welfare of the surrounding community